Understanding Jill McCorkle - Bennett, Barbara, 1959- (Understanding contemporary American literature., 2000)
"Understanding Jill McCorkle introduces readers to the novels and short story collections of Jill McCorkle's growing canon. Since 1984 McCorkle has written five novels, including The Cheer Leader and Carolina Moon, and two books of short stories - Crash Diet and Final Vinyl Days and Other Stories - entering the publishing world, as one reviewer noted, "with the literary equivalent of a rebel yell." Filling the gap of critical study on McCorkle, Barbara Bennett analyzes the widely read and admired output of this prolific southern writer. Bennett identifies and discusses the diverse characters, thematic concerns, and keen sense of language that distinguish McCorkle's work."--Jacket